Demography of Antarctic krill (Euphausia superba) from the KY1804 austral summer survey in the eastern Indian sector of the Southern Ocean (80 to 150˚E), including specific investigations of the upper surface waters - Schaafsma, Fokje L.; Driscoll, Ryan; Matsuno, Kohei; Sugioka, Rikuto; Driscoll, Sara; van Regteren, Marin; Sasaki, Hiroko; Matsukura, Ryuichi; van Franeker, Jan Andries; Murase, Hiroto (Frontiers in Marine Science, 2024)
Antarctic krill (Euphausia superba) is a harvested species that has an important role in the Southern Ocean food web. Knowledge on the demography of Antarctic krill is necessary for a better understanding of the distribution of life stages and their relation with predator species. In addition, such information is essential for krill fisheries management by CCAMLR (Commission on the Conservation of Antarctic Marine Living Resources). A large part of the Indian sector of the Southern Ocean is understudied and large-scale krill surveys of this region are scarce. Therefore, a survey was carried out during the austral summer of 2018/2019 on board RV Kaiyo-maru in the region from 80 to 150˚E. Krill was collected using a Rectangular Midwater Trawl (RMT). Previous studies suggest that part of the Antarctic krill population resides in the upper surface of the water column, but traditional trawls and echosounders have not been able to fully investigate this stratum due to sampling constraints. To overcome this knowledge gap, the upper surface (0-2 m) was sampled using a Surface and Under Ice Trawl (SUIT) in addition to the standard survey net. Results show that there were differences in the horizontal and vertical distribution of post-larval krill between the area west and east of approximately 120˚E. These differences coincided with variation in environmental properties. Early calyptopis larvae were found throughout the survey area. Their relatively low numbers suggested ongoing spawning that started early in the season. Juveniles were found mainly in the western side of the sampling area and large densities of this developmental stage were found to reside in the upper two meters of the water column. The quantitative estimation of krill in the upper surface indicated that undersampling this part of the population may influence estimates of, for example, recruitment.